Perbandingan Skin Preparation Kombinasi Alkohol 70% dan Chlorhexidine Gluconate 4 % dengan Kombinasi Chlorhexidine Gluconate 4% dan Povidone Iodine 10% terhadap Jumlah Koloni Kuman pada Persiapan Pembedahan - Slamet Riyanto; Kusman Ibrahim; Urip Rahayu (Jurnal Keperawatan Silampari, 2022)
This study aims to examine differences in the number of bacterial colonies after skin preparation using a combination of 70% alcohol and 4% chlorhexidine gluconate with 4% chlorhexidine gluconate and 10% povidone-iodine. This study used a quasi-experimental method with a pre-post test design. The results showed a decrease in the number of bacterial colonies by 99.84% in the 70% alcohol group and 4% chlorhexidine gluconate, and 99.77% in the 4% chlorhexidine gluconate and 10% povidone-iodine groups. While the difference in the number of bacterial colonies between the two groups, there was no significant difference with a p-value of 0.320 > 0.05. In conclusion, both groups effectively reduced germ numbers, but there was no significant difference in effectiveness between the two groups. Keywords: Alcohol, Chlorhexidine, Iodine, Skin Preparation